Government Readiness In The Implementation Of Accrual-Based Government Accounting Standards (Case Study At The Sumut DPRD Office) - Azka Rayyani; Yenni Samri Juliati Nasution (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2023)
This research is expected to be able to select the availability of public experts to apply accrual-based government accounting standards at the North Sumatra DPRD office. This research report examines the accessibility of financial planning at the DPRD office in North Sumatra. In addition, this content describes the problem of the accrual accounting cycle. The data collection strategy was based on perception, interviews, and documentation research. The results of data research using abstract methods are made from various perspectives. The results of this study indicate that workers in the DPRD office in North Sumatra generally know about the government's accrual accounting rules. The agreement, which is being prepared for implementation based on the annual financial report, will be jointly implemented at the North Sumatra DPRD office in the 2016 fiscal year.